Impact of early versus late tracheostomy on success or failure of ventilator weaning - Quirino, Alberto M.; Arrambi-Diaz, Cibeles; Ramirez, Jesus C.; Lugo, Juan A.; Morales, Jesus A.; Lopez, Rocio M. (International Journal of Research in Medical Sciences, 2024)
Background: Determine impact of early versus late tracheostomy on success or failure of ventilator weaning. This study is a cross-sectional, observational, descriptive, and analytical study. Method: Patients, clinical records of patients admitted to intensive care unit (ICU) in our hospital, weaned from invasive mechanical ventilation (IMV) after early versus late tracheostomy. Descriptive and inferential statistical analysis with Chi square (p<0.05), using SPSSv25.0 software. Time required after tracheostomy for ventilator weaning. Results: Positive significant association between ventilator weaning failure and prolonged difficult weaning process, indicate the importance of these factors in tracheostomy patients. Conclusions: According to this study, early tracheostomy reduces weaning failure and risk of ventilator-associated pneumonia.